Two new high-altitude subspecies of Tapinopterus (Tapinopterus) cognatus (Dejean, 1831) (Coleoptera: Carabidae: Pterostichinae) from Serbia - Ćurčić, Srećko; Ilić, Nastas; Vesović, Nikola; Antić, Dragan (Zootaxa, 2015)
The genus Tapinopterus Schaum, 1858 currently comprises around 60 species belonging to eight subgenera, inhabiting mostly the Balkan Peninsula and Asia Minor (Schatzmayr 1942, 1943; Bousquet 2003; Ćurčić et al. 2008; Arndt et al. 2011; Lohaj et al. 2012). The taxa live in limited geographic areas and are mostly montane (Trautner & Geigenmüller 1987; Guéorguiev & Guéorguiev 1998). The territory of Serbia is inhabited by two species of Tapinopterus, T. (T.) cognatus (Dejean, 1831) (recorded in Bulgaria and Romania as well) and T. (T.) miridita (Apfelbeck, 1904) (recorded in Albania and the Republic of Macedonia as well), as well as by the three subspecies, T. (T.) cognatus cognatus (Dejean, 1831) (known from Mt. Suva Planina in Serbia and from Bulgaria), T. (T.) cognatus winkleri Mandl, 1936 (known from the Svrljiške Planine Mts. and Mt. Stara Planina in both Serbia and Bulgaria), and T. (T.) miridita miridita (Apfelbeck, 1904) (known from Mt. Šar Planina in both Serbia and the Republic of Macedonia), respectively (Mandl 1936; Schatzmayr 1942, 1943; Guéorguiev & Guéorguiev 1995; Drovenik & Peks 1999; Bousquet 2003; Ćurčić et al. 2007; Guéorguiev & Giachino 2008). In our opinion, T. (T.) cognatus cognatus does not live in Bulgaria (as was previously reported) (Bousquet 2003), while the older Schatzmayr’s (1943) record “Klisura” should refer to the Iron Gate Gorge in SW Romania and NE Serbia, not to any Bulgarian place. The other mentioned locality, i.e., Mt. Suva Planina in Serbia, is situated far from the type locality (Iron Gate). Since nearly all Tapinopterus taxa are regional or local endemics, this southernmost record in SE Serbia for T. cognatus cognatus seems unlikely. In view of the high diversity of Tapinopterus on the Balkan Peninsula, it is expected that new taxa exist in border areas of the distribution in Serbia. During the last years, the first (SĆ), second (NI) and fourth author (DA) of the paper investigated a number of epigean montane habitats in SE and C Serbia in order to confirm such an assumption, by collecting a series of ground beetles at high altitude sites. After careful examination of the samples, we identified two Tapinopterus subspecies new to science.